Long-term remission after low dose radiotherapy in patient with extensive squamous cell carcinoma of the hand: A case report. Issue 39 (September 2016) - Cheo, Timothy; Ng, Ivy; Ooi, Kiat Huat; Ai Choo, Bok
Abstract: Rationale for Case Report: Cutaneous Squamous Cell Carcinoma (cSCC) of the hand is uncommon and tends to have poorer outcomes. Surgical resection with wide margins around the tumor is recommended as the treatment of choice, and radiotherapy is considered second-line treatment. Nodal evaluation involves dissection necessitating some morbidity. The role of less invasive modalities of nodal evaluation is not well established. Case Presentation: We report a case of locally advanced case of hand cSCC. Positron emission tomography-computed tomography (PET-CT) showed disease involving full thickness of the hand as well as the ipsilateral axillary node. To achieve adequate surgical margins would have necessitated amputation at the wrist, which the patient did not consent to. Instead, he was given a two-and-a-half week course radiotherapy to the hand without axillary radiation. With the radiotherapy treatment, he managed to achieve complete remission of disease while retaining full function of the hand, which was maintained at 22 months post-treatment. Main Lessons: CSCC of the hand is uncommon and challenging to treat. Radiotherapy is a highly effective treatment modality which is able to achieve functional preservation. Care should be taken when evaluating nodal status using PET-CT.